Low Tunnels inside Mediterranean Greenhouses: Effects on Air/Soil Temperature and Humidity - Alejandro López-Martínez; Francisco D. Molina-Aiz; María de los Ángeles Moreno-Teruel; Araceli Peña-Fernández; Fátima J. F. Baptista; Diego L. Valera-Martínez (Agronomy, 2021)
The main objective of this work was to analyze the microclimate generated inside a low tunnel (floating row cover) installed in an Almería-type greenhouse. Low tunnels are commonly used in the open field to protect plants against insect attack and to improve the production of muskmelon and strawberry. Floating row covers can also be used inside greenhouses during the first few weeks after the transplantation of muskmelon and watermelon crops in spring-summer cycles. This work was carried out during the first weeks of a watermelon culture (Citrullus lanatus Thunb.) growing with a polyethylene row cover inside an Almería-type greenhouse (2115 m2). Air temperature and humidity, plant temperature and soil temperature and humidity were measured in the greenhouse inside and outside the row covers. During the three days of measurement, all greenhouse vent openings were closed. The use of the low tunnels increased average air temperature around plants from 24.0 ± 9.0 °C to 26.9 ± 9.7 °C. A maximum difference in air temperature of about 5.9 °C was observed at noon. The average daily temperature of the crop was 28.2 ± 11.8 °C inside the row cover and 24.6 ± 8.9 °C without it. Similarly, the absolute humidity of air was clearly higher inside the low tunnel (0.0201 ± 0.0098 g/g) than around the plant rows without floating cover (0.0131 ± 0.0048 g/g). The soil temperature was also higher inside the low tunnel compared to the area without this second plastic cover. The effect of the tunnel decreased with depth, with average temperature differences of 1.2 ± 0.5 °C on the soil surface and 0.6 ± 0.5 °C at 20 cm depth.